A multi-column vertical mixing scheme to parameterize the heterogeneity of oceanic conditions under sea ice - Barthélemy, Antoine; Fichefet, Thierry; Goosse, Hugues; Madec, Gurvan (Ocean Modelling, 2016)
International audience